Morphological characterization, molecular identification and pathotyping of Colletotrichum Species in Peninsular Malaysia / Khor Bee Sym - Khor, Bee Sym (2013)

(untitled)
Nineteen isolates of Colletotrichum spp were obtained from infected fruits, 16 isolates were from Capsicum annuum, and three isolates from non-host of Capsicum annuum, which consist of one isolates from papayas and two isolates from strawberries. All showing anthracnose symptom. Growth rate can be the criteria for Colletotrichum identification. C. gloeosporioides has the fastest growth rate among the 3 species and C. acutatum has the slowest growth. C. truncatum has the average growth rates. ANOVA results showed that all of growth rate showed that there are significant different among the species. C. truncatum has the longest length of conidia (falcate) size and C. acutatum (fusiform) has the shortest length of conidia size. C. gloeosporioides (cylindrical) has the widest width compared to C. truncatum. ITS has identified six isolates as C. truncatum, five isolates of C. scovillei and five C. gloeosporioides complexes most likely as one Colletotrichum species, one C. asianum, one C. siamense and two C. queenslandicum. More gene sequencing work needed to clearly differentiate the species besides ITS region. Pathotypes studies have identified on wounded mature fruits were one pathotype on C. scovillei which were highly virulent on the genotype Capsicum annuum (Kulai) with host reaction of 7, three pathotypes were identified within C. truncatum infecting (Kulai and bell pepper) with host reaction of 5 to 9, four pathotypes were identified within C. gloeosporioides complex with only two isolates infecting Kulai and bell pepper, one isolates of Colletotrichum sp. and two isolates infecting only Kulai. All isolates from C. annuum used in this study showed no infection on the resistant genotypes C. chinense. Non-host Colletotrichum species were able to infect only the genotype Kulai.